Competition and Mobile Network Operator’s Investment Relationship: A Firm Level Empirical Evidence for Developing Countries - Ariansyah, Kasmad; Nuryakin, Chaikal (Journal of Telecommunications and the Digital Economy, 2019)
Policymakers have reformed the telecommunications market structure for several decades, from a monopoly to a more competitive market. They believed that the competitive market structure would be able to overcome the limitations of investment required to develop the industry and to provide equitable access. However, the advance of mobile broadband technology has triggered the emergence and proliferation of over-the-top (OTT) services that have considerably changed the competition landscape. First, in addition to acting as new competitors, the availability of OTT services also helps Mobile Network Operators (MNOs) to acquire more subscribers. Second, the competition has broadened to cross geographical boundaries. This paper aims to investigate the effect of the competition intensity on MNOs’ investment behaviour in the most recent context and focus only on MNOs in developing countries. The results show that competition intensity and MNO’s investment behaviour have an inverted U-shaped relationship with a turning point of 0.61. This points to the existence of competition intensity that maximizes the MNO’s investment. The empirical results also show the cumulative impact of the competition intensity on investment is 12.5 times of the immediate impact.